The Selection of the Rightly Guided Caliphs and Hallaq’s Perspective: A Research Review - Javed Iqbal; Dr. Faridah Yousuf; Usmat Batool (Indus Journal of Social Sciences, 2025)
Many contemporary Orientalists and Occidentalists have failed to present an accurate image of various Islamic principles. Among these scholars is Wael Hallaq, who, after Joseph Schacht, is considered a prominent name in the Western academic world. Born in 1955 in Nazareth, Palestine, Hallaq earned his B.A. from Haifa University in Israel and later travelled to the United States for his Master’s and PhD. He is the author of approximately 20 books and 80 articles. He has critically discussed the political, economic, social, and religious systems of Islam. Notably, he has raised objections regarding the selection process of the Rightly Guided Caliphs (Khulafā-e-Rāshidīn). According to his perspective, the Prophet Muhammad ﷺ did not appoint Abu Bakr al-Siddiq (RA) as his successor during his lifetime, which he considers the first political issue of the newly established Islamic state. He refers to the nomination of Umar ibn al-Khattab (RA) as "World Order II", acknowledges the selection of Uthman ibn Affan (RA) as aligned with Sunnah, and although he recognises Ali ibn Abi Talib (RA) as the fourth Caliph, he does not delve into his character. This article reviews Hallaq’s objections.